Code-Switching: Teacher Strategy in Arabic Learning - Adella Ira Wanti; Zakiyah Arifa (Universitas Islam Negeri Palangka Raya, 2022)
This study describes how code-switching between first language (L1) and foreign language (FL) is used as teaching strategy by teachers in Arabic learning. The method used in this study was a descriptive qualitative. The data sources were Arabic teachers in East Java and Bali. Data collection techniques used in this research were interviews and observations analyzed in three stages: reducing data, presenting data, and drawing conclusion. The result showed that Arabic teachers agreed that code-switching could be used as a teaching strategy to facilitate students' understanding of learning materials. Code-switching function can be applied in three aspects: 1) curriculum activity, 2) class management and 3) interpersonal relationship. Code-switching can be an essential part that Arabic teachers can utilize in carrying out the learning process in the classroom. Teachers can use it as an indirect strategy if using Arabic does not fulfill the learning objectives.